Large Optical Tunability of 5d 2D Electron Gas at the Spinel/Perovskite γ‐Al2O3/KTaO3 Heterointerface. Issue 20 (17th June 2022) - Qi, Shaojin; Zhang, Hui; Zhang, Jine; Gan, Yulin; Chen, Xiaobing; Shen, Baogen; Chen, Yuansha; Chen, Yunzhong; Sun, Jirong
Abstract: The 5d 2D electron gas (2DEG) in KTaO3 ‐based heterostructures exhibits stronger spin‐orbit coupling and higher superconducting transition temperature compared to the 3d SrTiO3 ‐based 2DEG, thus attracts much attention recently. However, compared to the intensively investigated isostructural perovskite‐type interfaces, the non‐isostructural 5d oxide interfaces remain less investigated. Herein, for the first‐time, epitaxial spinel/perovskite γ‐Al2 O3 /KTaO3 heterointerface is created, at a deposition temperature as low as 300 °C. Metallic 2DEG emerges at the interface when the thickness of γ‐Al2 O3 overlayer exceeds a critical thickness of approximately 2.4 nm. The interface states are found to be tuned largely by the light illumination, and the maximum change in the 2DEG carrier density under the light is 3 × 10 13 cm –2 . The light‐tunable spin‐orbit coupling exhibits a maximum strength of Rashba spin‐orbit coupling and spin‐splitting energy of ≈ 7.93 × 10 –12 eV m and ≈ 24.96 meV, respectively. Such remarkable photosensitivity of the non‐isostructural 5d 2DEG offers new opportunities for oxide optoelectronic devices. Abstract : The non‐isostructural spinel γ‐Al2 O3 (GAO) films can be epitaxially deposited on (001)‐oriented KTO single‐crystal substrates. A large change in the carrier density is 3 × 10 13 cm –2 upon light illumination. The light‐tunable spin‐orbit coupling exhibits a maximum strength of Rashba spin‐orbit coupling and spin‐splitting energy of ≈ 7.93 × 10 –12 eV m and ≈ 24.96 meV, respectively.